the relationship between complience use PPE eyes with metal welding chips in eyes welders in the welding workshop in boja - fatmasari, ikka fitria feby; musyarofah, siti; widjasena, baju (Jurnal Formil (Forum Ilmiah) Kesmas Respati, 2019)
Accident that occured in the workplace there are several interrelated causes can be a death cause, disable and work-related disease (WRD). Welders in welding workshop have some several eye injuries incident. One of them was metal welding chips. The use of PPE eyes is very importance for welders. Infact still many welders who neglect in this health. This study aim to determined the relationship between compliance use PPE eyes with metal welding chips on the eyes welders in the welding workshop in Boja village. This research used survey analytic research with cross sectional approach. The population in this study was all welders in welding workshop in Boja village. The sampling technique with total sampling that accorded to the inclusion criteria. The sample was 34 respondents. The instrument that was used were questionnaires and checklist sheets. The results indicated that the welders that compliance using PPE eyes as much as 44,1%. The welders rarely exposed by metal welding chips as much as 47,1%. The data analayzed with Chi-Square test there was significant relationship between compliance PPE eyes with metal welding chips on the eyes welders in the welding workshop in Boja village. {p value = 0,001; PR= 3,947 (1,4-11,2)} Based on result of the study, the welding workshop holders are being recommended to provide PPE eyes and supervise the use of PPE eyes for the welders